P-OGC61 Long-term outcomes following minimally invasive oesophago-gastric resection for oesophageal and gastro-oesophageal junctional cancer: a single center experience. (16th December 2021) - Orabi, Amira; Chillarge, Gauri; Di Mauro, Davide; Veeramootoo, Darmarajah; Mitchell, keith; Reece-Smith, Alex; Manzelli, Antonio; Daneshmend, Tawfique; Wajed, Shahjehan
Abstract: Background: Oesophago-gastric surgical resection for cancer has been associated with high morbidity and poor long-term prognosis. Medical advances have led to improvements and the con-current development of videoscopic technology enabled a paradigm shift in many areas of surgical practice. Between 2004 - 2010, a three-stage total (thoracoscopic/laparoscopic) minimally invasive oesophagectomy (MIO) with curative intent, was offered to all patients diagnosed and treated for esophageal and oesophago-gastric junctional (GOJ) cancers as an alternative to open surgery at our specialist Centre. Previously we have reported on safety, feasibility, short term outcomes, quality of life and complication profiles; this study now reports on eventualities at least a decade after surgery. Methods: All patients who underwent MIO (laparoscopic/thoracoscopic) three-stage procedure from April 2004 to January 2010 for oesophageal and GOJ malignancy were identified. A retrospective analysis of patients' records in conjunction with an updated clinical follow-up was carried out. Patients' demographics, oncologic stage (in accordance to the American Joint Committee on Cancer 6th and 7th Edition), overall survival, 5-year and 10-year survival, recurrence rate and disease-free survival (DFS) were retrospectively analyzed. Statistical analysis was conducted using Prism version 9.1.0 (GraphPad Holdings LLC, California). Results: A total of 120 patients (majority of which were males – 84.2%) were included in the study. Mean age was 66.7 ± 0.74. 43 patients. In-hospital death occurred in 4 (3.3%) patients. Over the time period, 25 (20.8%) patients were alive. Of those deceased Sixty-six (69.5%) succumbed to cancer, and 29 (30.5%) died from other causes. 43 patients (35.8%) were alive at 5 years and 33 (27.5%) at 10 years. Excluding those with Stage 0 disease, the 5-year and 10-year survival rates were 32.4% and 24.1%, respectively. The recurrence rate was 63 (52.5%) patients and the overall median DFS was 24 months (IQR, 186); Stage 3 patients had the shortest DFS (p < 0.0001). Conclusions: Survival and disease-free survival in this historical cohort of patients who underwent a total MIO for cancer is comparable to published data from similar open series of that era as well as modern reported outcomes from specialist centers. Benefits of a minimally invasive approach can therefore be realized without compromise to oncological and overall prognosis.